2022
DOI: 10.1177/00031348221091966
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age Alone on Outcome of Acute Surgical Conditions Among Healthy Patients (Non-smokers, Non-obese, and No Comorbid Conditions)

Abstract: Background The impact of age alone in relation to postoperative outcomes needs to be further elucidated. This study investigated whether increasing age was associated with increased morbidity and mortality for patients with no comorbidities undergoing acute care surgery (ACS). Methods The 2016-2018 National Surgical Quality Improvement Project database was used to identify adult patients who underwent ACS performed on an urgent/emergent basis. Patients overweight or with pre-existing medical comorbidities were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Shah et al 23 utilized the Nationwide Inpatient Sample administrative database and assessed the predictors of postoperative complications and mortality in a large national population of EGS patients and identified age as an independent predictor of mortality for all EGS diagnoses. Subsequently, Sebekos et al 24 showed that mortality increased by 1.14-fold for every decade after the age of 60 in older adults undergoing EGSPs. Castillo-Angele et al analyzed Medicare inpatient claims of 882 929 patients and showed that frailty and an increased CCI were associated with an increased risk of mortality, while larger hospital volume, specifically 200 beds or greater, was associated with a decreased risk of in-hospital mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Shah et al 23 utilized the Nationwide Inpatient Sample administrative database and assessed the predictors of postoperative complications and mortality in a large national population of EGS patients and identified age as an independent predictor of mortality for all EGS diagnoses. Subsequently, Sebekos et al 24 showed that mortality increased by 1.14-fold for every decade after the age of 60 in older adults undergoing EGSPs. Castillo-Angele et al analyzed Medicare inpatient claims of 882 929 patients and showed that frailty and an increased CCI were associated with an increased risk of mortality, while larger hospital volume, specifically 200 beds or greater, was associated with a decreased risk of in-hospital mortality.…”
Section: Discussionmentioning
confidence: 99%